Academic continuity: Staying true to teaching values and objectives in the face of course interruptions - Day, Terence (Teaching and Learning Inquiry, 2015)
Academic continuity planning is an emerging tool for dealing with class cancellation associated with natural disasters, acts of violence and the threat of pandemics. However, academic continuity can also be an issue with respect to less dramatic events, such as power outages, inclement weather, or the temporary unavailability of an instructor, especially if the problem is recurring. Many of the proposed alternative forms of delivery involve some form of web-based learning, but the extent to which these approaches work when students expect face-to-face delivery has not previously been examined. In one such interruption, web-based conferencing from home was undertaken. Based on average test scores, learning was unimpeded by web-based conferencing for one week, but there were some small gender effects that warrant further investigation. Many student comments reflected reduced engagement. The professor noted that students were more likely to respond to questions when the students could see the professor instead of the slides, but in general there were fewer student responses to questions than in face-to-face lectures. A number of comments made unsolicited comparisons with the traditional lecture format, suggesting that the context for teaching and learning, and students’ previous experience of different teaching approaches may merit more discussion in online learning studies.